Penerapan Decision Support System dalam Menentukan Karyawan Baru pada CV. Ria Printing Km 6.5 Menggunakan Metode Preference Selection Index - Rosi Rahmadi Syahputra; Dewi Suranti; Ricky Zulfiandry (Universitas Dehasen Bengkulu, 2022)
The recruitment process requires a professional and accurate way to produce human resources that can support the quality and successful of organization. The recruitment of new employees is an activity carried out at CV. Ria Printing when it requires additional workers or changes in workforce. So far, the new employee selection system is still done manually by looking at the highest score from prospective employees which usually lasts a long time, because the organization or company must first check and select the criteria and requirements that are completed by prospective employees carefully. In this situation, in selecting new employee, a decision support system is needed so that employee recruitment can be carried out more accurately. One method that can be applied in the desicion support system in determining new employees is Preference Selection Index Method. This method is useful for solving multi-criteria decision making, there is no need to assign relative importance between attributes and there is no need for computing attribute weights involved in decision making. The results obtained are based on the highest value in the application of Preference Selection Index using sample data of 10 people, so that 1st rank is Bella Grace with score of 0.96, 2nd rank is Adella Fitriansyah with score of 0.88 and third rank is Aedi Dicerita with score of 0.76. From the results of the high assessment, it can make it easier for the recipient of CV. Ria Printing KM 6.5 in making decisions to determine new employees.